10.36873/jht.v15i2.2171 PP.130-137 : Niko, Herlina Darwati, dan Slamet Rifanjani: KEANEKARAGAMAN JENIS GASTROPODA PADA EKOSISTEM HUTAN MANGROVE DI DESA SENTEBANG KABUPATEN SAMBAS KALIMANTAN BARAT (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2020)
Gastropods are a single shell mollusk phylum. Gastropods have a really significant function, particularly in the mangrove ecosystem. Mangrove forests are a very supportive habitat for gastropods. Gastropods have a very important role in the processof decomposing litter and maintaining nutrient dynamics in mangrove forests. This study aims to obtain and analyze data on the diversity of gastropods in the mangrove forest ecosystem in Sentebang Village, Jawai District, Sambas Regency. The research wasconducted in June 2020 using survey methods and data collection techniques using purposive sampling. Based on the results of the research that has been done, it was found that there were 11 types of gastropods from 5 families. The types of gastropods found were Nerita violacea, Cerithidea obtusa, Cerithidea cingulata, Littoraria melanostoma, Littoraria scabra, Littoraria angulifera, Pythia plicata, Ellobium aurisjudae, Cassidula nucleus, Cassidula aurisfelis, Spherassiminea miniata. The gastropod diversity index in line 1 = 1.2246, line 2 = 0.8689, and line 3 = 0.9554. Track 1 is in the medium category, for lines 2 and 3 it is in the low category. The overall diversity index is 1.6239 which is in the medium category. The similarity index for the types of gastropod lines 1 and 2 = 40%, lines 2 and 3 = 25%, lines 1 and 3 = 20% which are included in the low category. Abundance index of gastropod type line 1 = 21.8, line 2 = 5.3, line 3 = 5.1. The evenness index of the gastropods line 1 = 0.6834, line 2 = 0.6268, line 3 = 0.6892. The overall evenness index is 0.6772 which is categorized as an unstable community. The gastropod dominance index line 1 = 0.3684, line 2 = 0.5186, line 3 = 0.4748, line 1 and 3 are in the low category, while line 2 is in the high category. The overall dominance index is 0.2574 which is in the low category, meaning that no type dominates. Based on the data that has been obtained, it can be concluded that the diversity of gastropods in the mangrove forest ecosystem in Sentebang Village, Jawai District, Sambas Regency is classified as moderate.Keywords: Gastropods, mangrove forest, species diversity